Peran Guru dalam Mengatasi Kesulitan Membaca dan Menulis Siswa Kelas 1 di SDN Inpres Kaworo, Kabupaten Bima - Rosnani; Aggussalam; Abdul Haris (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to describe the early literacy skills of first-grade students at SDN Inpres Kaworo, Bima Regency, and to analyze various teacher efforts in overcoming students' reading and writing difficulties. This study focuses on aspects of letter recognition, phonemic awareness, spelling ability, and basic writing skills as the foundation of early literacy in elementary school students. This research method uses a qualitative approach with descriptive methods. The research subjects consisted of first-grade students and class teachers at SDN Inpres Kaworo, Bima Regency. Data collection techniques were carried out through observation, interviews, and documentation to obtain a comprehensive picture of students' literacy skills and the learning strategies implemented by teachers. Data analysis was carried out through the stages of data reduction, data presentation, and systematic drawing of conclusions based on field findings. The results of the study indicate that students' early literacy skills are at various levels, especially in letter recognition, phonemic awareness, spelling ability, and early writing skills. These differences in abilities cause variations in students' learning speeds during the learning process. Literacy barriers found include difficulty distinguishing similar letters, limitations in spelling words, and errors in capitalization and letter shapes that do not comply with rules. Supporting and inhibiting factors are also influenced by learning motivation, student concentration, classroom conditions, and family support at home. Teachers' efforts include implementing phonics and syllabication methods, using letter and picture cards, repeated reading exercises, gradual writing exercises, and individual correction. Learning strategies are reinforced with a differentiated approach, strengthening motivation, and creating a conducive classroom atmosphere. Parental involvement also supports the improvement of students' literacy skills. The final results show a gradual improvement in basic literacy skills in first grade students.